Społeczno-kulturowe imaginaria epidemii i ich reprezentacje – wybrane matryce teoretyczne eksploracji - Bielska, Ewa (Studia Edukacyjne, 2020)
The topic of analysis are socio-cultural imaginaries of the pandemic. The assumption is that the pandemic may be characterized by reference to the imaginaries and system of knowledge related to the disease as well as is located in modern and postmodern imaginaries of risk, post-Anthropocentrism and trajectory of socio-cultural trauma creation process. The socio-cultural exemplifications of the presented thesis are transmitted by the media representations of the Covid-19 pandemic. The paper is composed of three main parts. The first one analyses the notions of an imaginary and socio-cultural trauma representation, the second part presents in the light of sociological and humanistic theories some selected exemplifications of pandemic representations and the third part is a summary.